2016
DOI: 10.3396/ijic.v12i2.013.16
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B surface antigenaemia among healthcare worker in a private Nigerian tertiary health institution

Abstract: Hepatitis B virus (HBV) has long been recognized as an occupational risk for healthcare workers (HCWs) as a result of regular and routine exposure to blood and other body fluids in the course of their duties. The risk of occupational exposure to such infection has been the concerns of HCWs for years. This cross-sectional study aimed to determine the seroprevalence of Hepatitis B surface antigenaemia among HCWs, from various occupation categories, in Babcock University Teaching Hospital, Ilisan, Nigeria, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…This finding is not new. A study in Nigeria observed a similar trend of higher HBsAg positivity among sanitary workers in a Nigerian hospital [27] . Orderlies do not directly handle patients but are involved in day-to-day sanitation activities, including cleaning the hospital environment.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is not new. A study in Nigeria observed a similar trend of higher HBsAg positivity among sanitary workers in a Nigerian hospital [27] . Orderlies do not directly handle patients but are involved in day-to-day sanitation activities, including cleaning the hospital environment.…”
Section: Discussionmentioning
confidence: 59%
“…Investigators have reported varying national and risk group-specific estimates. Prior reports suggest a prevalence of 10-15% in the average risk Nigerian population (Elikwu et al, 2016). In Nigeria, investigators have found high HBV prevalence among surgeons (25.7%), voluntary blood donors (23.4%) and infants (16.3%) (Abiodun et al, 2017;Bakarey et al, 2018).…”
Section: Epidemiology Of Hepatitis B Virusmentioning
confidence: 99%